Mass Transfer during Osmotic Dehydration of Tunisian Pomegranate Seeds and Effect of Blanching Pretreatment - Basma Khoualdia; Samia Ben-Ali; Ahmed Hannachi (International Journal of Chemical Engineering)
In this work, the osmotic dehydration (OD) of Tunisian pomegranate seeds of “El Gabsi” variety was investigated. To optimize the process operating conditions, the effect of temperature, hypertonic solution solid content, and stirring speed was studied. The best conditions resulting in the higher water loss and the minimum of fruit damages found are 40°C, 50°Bx, and 440 rpm. In these conditions, the effect of blanching pretreatments on the solute and water transfer kinetics during the OD was investigated. The blanching pretreatments were carried out using two methods: blanching in a boiling water bath and in a microwave oven. The mass diffusion kinetic depends on time, temperature, hypertonic solution solid content, stirring speeds, and pretreatment process. Peleg’s model showed a good fit to the experimental data. By applying blanching pretreatments, the water and solute effective diffusivities passed from the order of 10−9 to the order of 10−8, and the OD equilibrium time was significantly reduced.